(untitled) (International Journal of Multidisciplinary Engineering In Current Research, 2025)
In today’s era of personalized wellness and digital convenience, recommending appropriate skincare products tailored to individual needs has become both a scientific and technological challenge. This project focuses on the development of an intelligent skin care product recommendation system that leverages user-specific data such as skin type, concerns (e.g., acne, dryness, sensitivity), environmental conditions, and lifestyle habits. By utilizing machine learning algorithms and dermatological databases, the system analyzes input parameters to suggest the most suitable skincare routines and products. It aims to address common issues of product mismatch and allergic reactions by offering recommendations grounded in evidence-based skin science. The integration of AI not only enhances the accuracy of suggestions but also provides users with real-time feedback and updates based on seasonal or behavioral changes. This project holds significant potential in transforming the skincare industry by enabling personalized, data-driven decisions that improve skin health and user satisfaction.